The role of active perinatology in the prevention of unnecessary loss of conceptus and birth rate drop - Dugalic, Stefan; Stanisavljevic, Dejana; Petronijevic, Milos; Stefanovic, Aleksandar; Vrzic-Petronijevic, Svetlana; Stefanovic, Katarina; Gutic Vukobrat , Bojana; Gojnic , Miroslava; Macura, Maja; Bozic, Dragana; Stanisavljevic, Tamara; Petronijevic, Milica; et al. (Medical Research, 2022)
Introduction: Modern perinatology demands continuous improvement of doctrines and protocols. The loss of conceptus is unforgivable while the possibility to sustain such pregnancy would elevate the level of birth rate that we aspire as a society in whole. The aim of this study was to describe the burden of pregnancy losses among women with inherited thrombophilias. Methods: The study included all women with inherited thrombophilia referred to Clinic for Gynecology and Obstetrics of the Clinical Centre of Serbia between 2016 and 2018 and followed-up to delivery. The patients were divided into two groups. Results:The total number of 180 patients had their first pregnancy while 178 patients had previous pregnancies. In 153 out of 178 patients, the previous pregnancy had poor outcome. 12 patients with AC therapy had FMU in previous pregnancies, 49 patients had missed abortion, 54 patients had second trimester miscarriage, 4 patients had both FMU and missed abortion, 9 patients had missed abortion and second trimester miscarriage while one patient had FMU, missed abortion and second trimester miscarriage. In previous pregnancies, 92 babies were born out of 313 pregnancies while in the current pregnancies treated with therapy there were 173 babies from 151 pregnancies. Conclusions: Patients with anticoagulant treatment in current pregnancy have had significant burden of previous pregnancy losses. Keywords: pregnancy; pregnancy losses; inherited thrombophilias.